Regeneration and characterization of self-pollinated crops at ICARDA – Best practices and considerations - Tsivelikas, Athanasios (International Center for Agricultural Research in the Dry Areas, 2023)
Regeneration and characterization of self-pollinated crops at ICARDA – Best practices and considerations